The Immediate Impact of COVID-19 on Law Enforcement in the United States - Jennings, Wesley G. (American journal of criminal justice, 2020)
During pandemics, like COVID-19, law enforcement agencies are responsible for working with government and public health officials to contain spread, serve the local community, and maintain public order. Given the person-to-person spread of COVID-19 through respiratory droplets, law enforcement officers are also at a heightened risk of exposure due to their close contact with members of the public. To protect officers, the Centers for Disease Control and Prevention (CDC) and other agencies have made numerous recommendations for law enforcement agencies to protect officers and the public. Departments around the country have responded to the pandemic in various ways, such as reassigning personnel to high-traffic areas, suspending training, roll calls, and community outreach initiatives, only issuing citations for low-level crimes, implementing safety precautions for officers, and limiting access to department facilities. The COVID-19 pandemic also has exposed some key obstacles for law enforcement, related to communication, resource management, the enforcement of public health restrictions, and changes to crime and service patterns. Based on these early/initial responses and obstacles during the COVID-19 outbreak, the current paper highlights directions for future responses to pandemics to ensure the safety and security of police officers and the communities they serve.